Interleukin-8 concentrations in obstructive sleep apnea syndrome: A systematic review and meta-analysis - Xiaoyan Li (Taylor & Francis Group, 2021)
Interleukin (IL)-8 has been shown to play an important role in obstructive sleep apnea syndrome (OSAS). However, its role in OSAS development is still controversial. This meta-analysis was to explore the correlation between interleukin (IL)-8concentration and OSAS. Database (from the inception to July 2021) searches on PubMed, Web of Science, Medline, EMBASE, and Cochrane Library were conducted for studies analyzing the correlation between IL-8 concentration and OSAS, regardless of the language of publication. Standardized mean difference (SMD) and 95% confidence intervals (CI) were used to analyze any prospective association between IL-8 concentration and OSAS.A total of 25 eligible studies, including 2301 participants and 1123 controls, were included in this meta-analysis. The included studies evaluating the association between serum IL-8 concentration and OSAS indicated that adults and children with OSAS had elevated serum concentrations of IL-8 compared with controls (SMD = 0.997, 95% CI = 0.437-1.517, P<0.001; SMD = 0.431, 95% CI = 0.104-0.759, P = 0.01). Categorization of the study population into subgroups according to body mass index, apnea-hypopnea index (AHI), ethnicity, and sample size also showed that individuals with OSAS had elevated serum concentrations of IL-8 compared with controls. Additionally, the results demonstrated that higher the AHI, higher was the IL-8 concentration. Similar results were observed in the literature on the association between plasma IL-8 concentration and OSAS. This meta-analysis verified that compared with controls, children and adults with OSAS have significantly elevated IL-8 concentrations.